2017
DOI: 10.5539/ijbm.v12n6p111
|View full text |Cite
|
Sign up to set email alerts
|

Leadership and Communication in HCMC, Vietnam

Abstract: Vietnam remains an exciting investment destination. Long term success in this East Asian country, however, requires effective management of resources including employees. This paper examines the literature and interviews with local employees in Ho Chi Minh City, Vietnam to identify cross-cultural communication and leadership issues at the international workplaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…When one party neglects the roles in a reciprocal relationship, hostility and disappointment are guaranteed (Pellegrini and Scandura 2008). Additionally, respect is most imperative in Vietnamese work settings as it significantly influences work communication within leader-follower-co-worker relationships (Weng 2017). Without the reciprocal respectful relationships between the leader and the followers, organizational members remain silent about raising and solving organizational problems due to a lack of trust towards the management (Weng 2017).…”
Section: Respect and Employee Outcomesmentioning
confidence: 99%
See 3 more Smart Citations
“…When one party neglects the roles in a reciprocal relationship, hostility and disappointment are guaranteed (Pellegrini and Scandura 2008). Additionally, respect is most imperative in Vietnamese work settings as it significantly influences work communication within leader-follower-co-worker relationships (Weng 2017). Without the reciprocal respectful relationships between the leader and the followers, organizational members remain silent about raising and solving organizational problems due to a lack of trust towards the management (Weng 2017).…”
Section: Respect and Employee Outcomesmentioning
confidence: 99%
“…Additionally, respect is most imperative in Vietnamese work settings as it significantly influences work communication within leader-follower-co-worker relationships (Weng 2017). Without the reciprocal respectful relationships between the leader and the followers, organizational members remain silent about raising and solving organizational problems due to a lack of trust towards the management (Weng 2017). Leck and Galperin (2006) found that the culture of collectivism has helped targets of bullying receive collective outward support from their peers, including supervisor and co-workers, to report bullying acts or has enabled peers to tell the perpetrator to stop the bullying behaviour.…”
Section: Respect and Employee Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Among East Asian nations, Vietnam is renowned for its diverse cultural perspectives owing to historical circumstances such as the impact of Confucianism arising from a thousand years of Chinese dominance co-existing with the Western cultural values emerging from the French and American occupations that lasted over a century (Tran et al ., 2016). Collectivism is one of the most prominent features of Vietnamese culture (Tiong Weng, 2017), as determined by an analysis of the five cultural aspects proposed by Hofstede (2001): power distance, uncertainty avoidance, individualism versus collectivism, masculinity versus feminism and future orientation. These cultural values have had a substantial influence on the management and leadership effectiveness of all Vietnamese companies (Tran et al ., 2016).…”
Section: Theoretical Foundation and Hypothesis Developmentmentioning
confidence: 99%